The Effect of YouTube Video on Students’ Listening Comprehension Performance - Qomariyah, Siti Syafi'atul; Permana, Dira; Hidayatullah, Heri (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
The difficulties to catch any intended information conveyed by speakers on the audio recording by the students still become problematic during learning listening comprehension in the classroom. This study aimed to find out the effect of applying YouTube videos on the students’ listening comprehension performance. This study was experimental research (quasi-experimental with non-equivalent control group design). The researchers used all the first-semester students of English language education as a sample through the total sampling technique. To get the data, the researchers used a listening test as the instrument. There were two groups that were tested in the study; experimental and control groups. The experimental group was treated by applying YouTube videos while the control group was treated by Audio recording. Based on the result of the study, it was found that the t-test was 1.834 and the t-table was 0.073 (t-test was higher than t-table). In the other words, the alternative hypothesis was accepted and the null hypothesis was rejected. The result of the study also showed that the students felt more interested and motivated to learn listening comprehension by using YouTube videos as the learning media during the learning process takes place in the classroom. Thus, it could be concluded that the application of YouTube videos has given a positive and significant effect on students’ listening comprehension performance.